OBESITY AS A CHRONIC INFLAMMATORY DISEASE: ADIPOSE TISSUE PATHOPHYSIOLOGY, PHARMACOLOGICAL REVOLUTION, AND MULTIDISCIPLINARY TREATMENT STRATEGIES - Lucjan Kocemba,; Piotr Rachwał,; Idalia Myszor,; Michał Madej,; Maria Kubacka,; Gabriela Mroczka,; Sylwia Nycz-Jucha,; Paulina Łobaza,; Brygida Pinkowicz,; Barbara Nowak-Misiąg, (International Journal of Innovative Technologies in Social Science, 2025)
Obesity is a global epidemic and a complex chronic neurohormonal disease, which is the main cause of lifestyle diseases. The aim of this review is to thoroughly collect and critically evaluate the latest information on the pathophysiology of obesity, including the importance of low-grade inflammation (meta-inflammation), as well as to analyze the effectiveness of breakthrough, multidirectional treatment methods. We conducted a narrative review of scientific literature from major medical databases, focusing on studies published between 2015 and 2025 that addressed pathogenesis, clinical consequences (cardiovascular disease, oncology), modern pharmacotherapy (GLP-1/GIP agonists), and bariatric surgery.Obesity is driven by adipose tissue (endocrine organ) dysfunction and chronic inflammation (metaflammation), leading to insulin resistance and gut-brain axis dysregulation. Modern pharmacotherapy, in particular GLP-1/GIP agonists, achieves weight loss of 15-22% (in STEP/SURMOUNT studies), which is comparable to the effects of early bariatric surgery. Surgery remains the most effective method of weight reduction and remission of metabolic complications. Effective treatment of obesity requires a personalized approach in which new pharmacology, lifestyle modification, and bariatric surgery must be integrated. The need for continuous, long-term treatment is crucial for maintaining weight and combating weight regain.